Shockwave application enhances the effect of dentin desensitizer. Issue 1 (January 2021) - Lee, Chang-ha; Jo, Seol-Ah; Kang, Kyongok; Dhont, Jan; Ferracane, Jack; Lee, In-bog
Abstract: Objectives: The purpose of this study was to develop a new device that can improve the effect of desensitizer using shockwaves and to verify its efficacy. Methods: A micro-shockwave generator was developed using a piezoelectric actuator (PIA-1000, piezosystem jena GmbH, Jena, Germany), an Arduino Uno microcontroller (Arduino, Torino, Italy), and a high voltage pulser (HVP-1000, piezosystem jena GmbH) at 700 V (400 A) and 100 μs. The occlusal surfaces of 20 extracted human upper and lower third molars without caries or restoration were reduced to expose the occlusal dentin, and the prepared occlusal surfaces were acid-etched with 32% phosphoric acid to remove the smear layer. The tooth specimens were connected to a fluid flow measurement instrument (nanoFlow, IB SYSTEMS, Seoul, Korea), permeability through dentin via dentinal fluid flow (DFF) was measured for 300 s, and the average DFF rate (Baseline DFF rate) was calculated. A desensitizer (SuperSeal, Phoenix Dental, Fenton, MI, USA) was applied to the acid-etched occlusal dentin surface of 10 randomly selected tooth specimens, left for 10 s, and rubbed with a microbrush for 30 s (Group 1). For the remaining teeth, the desensitizer was applied, and a shockwave (100 μm stroke, 10, 000 G) was applied for 10 s (2 shots/s) and rubbed with a microbrush for 30 s (Group 2). After desensitizer application, subsequent DFF was measured for 600 s, and the average DFF rate was calculated (post-application DFF rate). DFF was continuously measured in real-time at 25 ± 0.5 ℃ under a hydrostatic pressure of 25 cm. The percentage reduction in DFF rate after desensitizer application (with or without shockwave) was calculated with respect to baseline DFF rate. Data were analyzed with independent t -test ( α = 0.05). Results: For all tooth specimens, DFF rate decreased after desensitizer application irrespective of the presence of shockwaves. The percentage reduction in DFF rate of SuperSeal with shockwave (Group 2) was 42.8 ± 19.0%, which was significantly higher than the 26.2 ± 13.6% of the SuperSeal only group (Group 1) (p < 0.05). Significance: Measurement of DFF change in real-time shows that shockwaves can help reduce dentin permeability beyond that SuperSeal dentin desensitizer produced alone.